2020
DOI: 10.1111/ene.14522
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental activities of daily living and neuropsychological functioning among patients with different types of cancer

Abstract: Background and objectives: The ability to perform instrumental activities of daily living (IADL) is important for maintaining independent living, and optimal health-related quality of life and well-being. Neuropsychological measures are predictors of IADL ratings. The aims of the present study were to measure ability to perform IADL in patients with cancer and to explore the relationship between IADL and neuropsychological functioning. Methods: We evaluated IADL in 182 patients with four different types of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…A majority of participants felt that there were times when they did not get enough rest or sleep. This information is consistent with the current literature regarding occupations (Chen et al, 2022; Megari, 2021; Neo et al, 2017). The occupation of rest and sleep was desired and often necessary for participants who reported sleep difficulties, low energy level, and resulting fatigue.…”
Section: Discussionsupporting
confidence: 93%
“…A majority of participants felt that there were times when they did not get enough rest or sleep. This information is consistent with the current literature regarding occupations (Chen et al, 2022; Megari, 2021; Neo et al, 2017). The occupation of rest and sleep was desired and often necessary for participants who reported sleep difficulties, low energy level, and resulting fatigue.…”
Section: Discussionsupporting
confidence: 93%
“…Because of the above, some researchers suggest that it should be more correct if we use the term cancer-related cognitive dysfunction. 12 In addition, author (2020a) has found that breast cancer patients who received chemotherapy performed worse in cognitive tasks including attention, memory, executive functions and language 13 compared to patients with prostate, colorectal or thyroid cancer. Moreover, breast cancer patients had significantly greater difficulty in performing IADL compared to patients with other types of cancer.…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…2 Ahora bien, las estrategias terapéuticas contra el cáncer con intención de curar interfieren con la integridad del cuerpo, por lo que los pacientes pueden experimentar múltiples síntomas como resultado de estos tratamientos, además de los síntomas propios de la enfermedad, afectando el funcionamiento y el bienestar del paciente, lo que conlleva a la disminución en la calidad de vida (CdV). [3][4][5] A lo largo del tiempo se ha investigado sobre CdV desde diferentes enfoques, haciendo énfasis en el significado que las personas le dan al aspecto socioeconómico. 6,7 No obstante, recientes investigaciones incluyen otros elementos que pueden influir en la apreciación de la CdV como son las condiciones físicas, psicológicas y sociales, concibiendo más holística la concepción que se tiene de esta.…”
Section: Introductionunclassified